Pharmacokinetics and skin concentrations of lincomycin after intravenous and oral administration to cats - Albarellos, Gabriela A. (2013)
The aim of the present study was to describe the plasma pharmacokinetic profile and skin concentrations of lincomycin after intravenous administration of a 15% solution and oral administration of 300 mg tablets at a dosing rate of 15 mg/kg to cats. Susceptibility of staphylococci (n = 31) and streptococci (n = 23) strains isolated from clinical cases was also determined. Lincomycin plasma and skin concentrations were determined by microbiological assay using Kocuria rhizophila ATCC 9341 as test microorganism. Susceptibility was established by the antimicrobial disc diffusion test. Individual lincomycin plasma concentration-time curves were analysed by a non-compartmental approach. After intravenous administration, volume of distribution, body clearance and elimination half-life were 0.97 L/kg ± 0.15 L/kg, 0.17 L/kg ± 0.06 L/h.kg and 4.20 h ± 1.12 h, respectively. After oral administration, peak plasma concentration, time of maximum plasma concentration and bioavailability were 22.52 μg/mL ± 10.97 μg/mL, 0.80 h ± 0.11 h and 81.78% ± 24.05%, respectively. Two hours after lincomycin administration, skin concentrations were 17.26 μg/mL ± 1.32 μg/mL (intravenous) and 16.58 μg/mL ± 0.90 μg/mL (oral). The corresponding skin: plasma ratios were 2.08 ± 0.47 (intravenous) and 1.84 ± 0.97 (oral). The majority of staphylococci and streptococci tested in this study were susceptible to lincosamides (87.09% and 69.56%, respectively). In conclusion, lincomycin administered orally at the assayed dose showed a good pharmacokinetic profile, with a long elimination half-life and effective skin concentration. Therefore, it could be a good first option for treating skin infections in cats.